Investigation of Combustion Characteristics of a Cottonseed Biodiesel Fuelled Diesel Engine. (2016) - Shelke, Pankaj S.; Sakhare, Nitin M.; Lahane, Subhash
Abstract: Diesel engines are very well known for their high torque and high thermal efficiency. But, the increase in demand of energy, rapid depletion of fossil fuels and meeting the stringent emission regulations, the researchers take interest to derive the alternative fuels from renewable resources. Among from all the different alternative fuels, vegetable oil has potential to substitute the traditional diesel fuels. The well-established transesterification process is generally used for the production of biodiesel from vegetable oil. In transesterification process the tri-glycerides are converted into mono glycerides with the help of alcohol and catalyst under certain temperature. In the present research work cottonseed vegetable oil is used to produce biodiesel by transesterification process using methanol and KOH as catalyst. As diesel engine combustion is heterogeneous spray combustion, it is very complex phenomenon. The physico-chemical properties of biodiesel are slightly different from diesel fuel. It is very interesting to study the combustion characteristics of a cottonseed based biodiesel fuelled diesel engine. This was the main motivation to take up this study to understand and analyze the combustion characteristics of a cottonseed biodiesel fuelled diesel engine. The experiment was carried out on a single cylinder diesel engine for base diesel and cottonseed biodiesel blends (B5, B10, B15, and B20) as a fuel. The combustion characteristics such as ignition delay, start of combustion, premixed, diffusion and after burning combustion phases, end of combustion and combustion duration were analyzed and compared with base diesel. It was observed that ignition delay and maximum rate of pressure rise decreased with biodiesel as compared to base diesel due to higher cetane number of biodiesel blends which confirms the smooth running of the engine. Ignition delay decreased from 11°CA with base diesel to 6.5°CA with B20 biodiesel. The start of combustion was advanced with all biodiesel blends due to higher bulk modulus results in automatic advance in dynamic injection timing and lesser ignition delay. The combustion duration was longer with all biodiesel blends as compared to base diesel due to longer injection duration results in poor performance of the engine with biodiesel blends.